Explanatory Power of the Tullock Contest as an Integral Part of Game Theory in Political Advertising Spendings - Mach, Petr; Cermakova, Klara (Yugoslav Journal of Operations Research; Online first, 2025)
This article deals with a concept known as the Tullock contest, frequently applied to game theory decision-making in lotteries, lobbying, advertising, the military, politics, biology and other areas. While the theory of the prisoner's dilemma explains that the rational choice of players is to defect with a resulting payoff that is lower than what would flow from cooperation, the Tullock contest is a model that explains what the value of the chosen strategy will be and what the resulting payoff will be. The Tullock contest is developed here in the context of the prisoner's dilemma and game theory. Best response functions of the Tullock contest are derived both algebraically and graphically, and the Nash equilibrium is shown. This paper confirms that some of prisoner’s dilemma games may be characterized as Tullock contests. We propose an explanation for high advertising expenditure in political campaigning games and we offer a numerical example of the equilibrium expenditure resulting in some positive payoff for each player. We prove that, on the other hand, international environmental agreements cannot be characterized as Tullock contests, thus prisonner’s dilemma game in these cases end up in a defect-defect Nash equilibrium with a payoff of zero for each player.